Changes in nitrate accumulation mechanisms as PM2.5 levels increase on the North China Plain: A perspective from the dual isotopic compositions of nitrate. (January 2021) - Luo, Li; Zhu, Ren-guo; Song, Cong-Bo; Peng, Jian-Fei; Guo, Wei; Liu, Yonghui; Zheng, Nengjian; Xiao, Hongwei; Xiao, Hua-Yun
Abstract: Nitrate ( NO 3 − ) has become recognized as the most important water-soluble ion in fine particulate (PM2.5 ), and has been proposed as a driving factor for regional haze formation. However, nitrate formation mechanisms are still poorly understood. In this study, PM2.5 samples were collected from September 2017 to August 2018 in Shijiazhuang, a city located on the North China Plain, and NO 3 − concentration, δ 18 O- NO 3 − and δ 15 N- NO 3 − values in PM2.5 were analyzed. NO 3 − concentrations increased as PM2.5 levels increased during both polluted and non-polluted days over the entire year. δ 18 O- NO 3 − values during cold months (63.5–103‰) were higher than those during warm months (50.3–85.4‰), these results suggested that the nitrate formation pathways shifted from the NO2  + OH (POH ) in warm months to the N2 O5  + H2 O (PN2O5 ) and NO3  + VOCs (PNO3 ) pathways in cold months. Especially during cold months, δ 18 O- NO 3 − values increased from 65.2–79.9‰ to 80.7–96.2‰ when PM2.5 increased from ∼25 to >100 μg/m 3, but when PM2.5 > 100 μg/m 3, there were relatively small variations in δ 18 O- NO 3 − . These results suggested that nitrate formation pathways changed from POH to PN2O5 and PNO3 pathways when PM2.5 < 100 μg/m 3, but that PN2O5 and PNO3 dominated nitrate production when PM2.5 > 100 μg/m 3 . Higher δ 15 N- NO 3 − values in warm months (−11.8–13.8‰) than in cold months (−0.7–22.6‰) may be attributed to differences in NOx emission sources and nitrogen isotopic fractionation among NOx and NO 3 − . These results provide information on the dual isotopic compositions of nitrate to understand nitrate formation pathways under different PM2.5 levels. Highlights: One-year values of δ 18 O- NO 3 − and δ 15 N- NO 3 − in PM2.5 were analyzed in Shijiazhuang. Seasonal variations in δ 18 O- NO 3 − were affected by various nitrate formation pathways. NO 3 − production shifted from POH to PN2O5+NO3 in cold months with increased PM2.5 Seasonal δ 15 N- NO 3 − was regulated by NOx sources and nitrogen isotopic fractionation.